2020
DOI: 10.35596/1729-7648-2020-18-4-96-112
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the potential electromagnetic pollution level and the danger of COVID-19. 4G/5G/6G can be safe for people

Abstract: The COVID-19 pandemic, spanning the globe, caused the death of hundreds of thousands of people and crisis in global economy. I found confirmation of the hypothesis that the level of environmental electromagnetic pollution affects the lethality rate of a population from COVID-19. I found a correlation between the degree of severity of hygienic regulation of levels of radio frequency electromagnetic fields for population, the main sources of which are mobile (cellular) communication systems, and the lethality ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…A recent Russian study found a strong correlation between a country's exposure limits for RF radiation and COVID-19 deaths per million (r=0.577) and deaths per cases (r=0.551) [24].…”
Section: Covid-19 Anomalies and Wireless Radiationmentioning
confidence: 98%
“…A recent Russian study found a strong correlation between a country's exposure limits for RF radiation and COVID-19 deaths per million (r=0.577) and deaths per cases (r=0.551) [24].…”
Section: Covid-19 Anomalies and Wireless Radiationmentioning
confidence: 98%
“…[323][324][325][326][327] The possible interaction of 5G technology with human health is being debated as well, raising contrasting speculations and evidence, mostly due to the limited knowledge about this relatively new EMF typology. 328,329 More recently, a few specific papers focused on the possible role of peculiar types of EMF in SARS-CoV-2 pathogenicity, 330,331 and a recent publication has presented some data about the detrimental interaction of radiofrequencies specifically with VGCC and with cation metabolism, erythrocytes, hemoglobin, coagulation, immune system and oxidative stress. 332 In view of the role of both the cell membrane electro-chemical changes and the cations in COVID-19, some more research could be performed to assess any possible inter-relationship of polluting environmental factors with VGCC, cellular membrane and cytoplasm ionic changes.…”
Section: G) Hemoglobin Hemementioning
confidence: 99%
“…[321][322][323][324][325] The possible interaction of 5G technology with human health is being debated as well, raising contrasting speculations and evidence, mostly due to the limited knowledge about this relatively new EMF typology. 326,327 More recently, a few specific papers focused on the possible role of peculiar types of EMF in SARS-CoV-2 pathogenicity, 328,329 and a recent publication has presented some data about the detrimental interaction of radiofrequencies specifically with VGCC and with cation metabolism, erythrocytes, hemoglobin, coagulation, immune system and oxidative stress. 330 In view of the role of both the cell membrane electro-chemical changes and the cations in COVID-19, some more research could be performed to assess any possible inter-relationship of polluting environmental factors with VGCC, cellular membrane and cytoplasm ionic changes.…”
Section: G) Hemoglobin Hemementioning
confidence: 99%